The Eulogy of Symeonic Miscellany: the Imperial Patronage of the First Slavic Anthology - Garzaniti, Marcello (Studia Ceranea, 2021)
The essay proposes an interpretation of the eulogy of Symeon’s Miscellany considering not only the cultural context of the First Bulgarian Empire at the beginning of the tenth century, but also the historical situation and the literary production of the seventies and eighties of the previous century when the Greek original of the Miscellany known by the name of the Soterios was conceived in Constantinople. This eulogy helps us to better understand the reasons that led to the creation of the Slavic version of this anthology at the time of Symeon. In the Constantinopolitan environment, this anthology was conceived as an adequate tool of the kind required by monks and priests engaged in the education of the laity, with particular focus on the foundations of orthodox doctrine. In the new environment the initiative was taken by Tsar Symeon, who – on the strength of his theological training – assumed a decisive role while occupying the throne by taking responsibility for directly instructing the Bulgarian aristocracy, fully exploiting a tool in the Slavic language that would have been very useful.